The Navajo blanket - Kahlenberg, Mary Hunt; Berlant, Anthony (Praeger Publishers, Inc. in association with the Los Angeles County Museum of Art, 1972)
Given in memory of Ethel A. Tsutsui, Ph.D. and Minoru Tsutsui, Ph.D.